(untitled) (Research, Society and Development, 2020)
Low back pain is one of the major causes of disability and absence in services and schools. At young age, low back pain is similar to that of adults, and is associated with seeking professional help, medication use, school absenteeism, reduced physical activity and health-related quality of life. This is a Bibliographic Review, aiming to investigate the characteristics and risk factors of low back pain in young people. Articles written in Portuguese and foreign languages were included in the electronic databases LILACS, PubMed, SPORTDiscus, SciELO, PEDro. The keywords used were: Young people, chronic low back pain, risk factors. The survey began in August 2019 and ended at the beginning of September. The variables of interest were noted by the author. A total of 16 articles were selected, 8 excluded and 8 included, all from 2010 to the recent year. The types of studies were Bibliographic Review, descriptive cross-sectional and observational cross-sectional study, with the total sample, ranging from 52 to 1597 female and male individuals. Several factors, according to the selected literature, were associated with low back pain in young people, such as physical inactivity, postures maintained for long periods, psychological factors and female gender. The literature review showed that low back pain in young people is associated with factors such as physical inactivity, postures maintained for long periods, psychological factors, negative symptoms and female gender.